PEMBELAJARAN MENULIS PUISI - Munaris, Munaris (Jurnal Bahasa Lingua Scientia, 2012)
In general, learning how write a poem can be conducted in two ways: structured, and free writing. Usually those strategies are done without a well-planned procedure. However, ideally a learning process must be well-planned and conducted using clearly-procedural strategies. Munaris 1 Strategy can be the alternative in teaching how to write simple poems and has been well-proven since it has been applied. This strategy concists of four steps: making description of photograph, arranging sentences into lines, simplifying the sentences, and filling out the ideas of the poems. This strategy can be adopted by teachers as personal practices and technique to teach the students to write poems.